Purchase Decision: Was It Affected By Product Innovation? (Purchases In Sour Sally Gandaria City South Jakarta) - Osman, Ismeth Emier; Mustika, Amalia; Budiono, Anita (Jurnal Penelitian Pariwisata, 2020)
Product innovation is the functional progress of a product that can make the product better than competitors' products. At least the newest product is better than the previous product. Because if a product has advantages, it will be seen as added value for consumers. This research aims to find out product innovations that influence consumer decision-making in buying Youghurt at Sour Sally. This research uses the descriptive correlational method. This study's population are all consumers who have shopped Black Sakura and White Skim at Sour Sally Gandaria City Jakarta. The sampling technique used is non-probability sampling, and the total number of respondents in this study was 89 people. To see the relationship level, the correlation coefficient of 0.662 means that the correlation of product innovation on purchasing decisions at Sour Sally Gandaria City Jakarta is strong and positive. So the purchasing decisions at Sour Sally Gandaria City Jakarta are influenced by product innovation by 43.82% and 56.18% influenced by other variables not examined in this study. Keywords: Product Innovation, Purchasing Decisions